Dynamics of chlorophyll in aging cotyledon leaves of Linum usitatissimum exposed to x-ray radiation - Berestyana, A.М.; Grodzinsky, D.M. (Reports of the National Academy of Sciences of Ukraine, 2014)
The dynamics of the chlorophyll pattern during aging cotyledons Linum usitatissimum irradiated with different doses of acute X-ray irradiation is investigated. The dependence of the degradation of chlorophyll a and chlorophyll b on doses and ontogenetic stages of cotyledon leaves is found. The features of the decay of chlorophyll as one of the parameters of radiation-induced aging are considered.